Estimating and controlling the traffic Impact of a collaborative P2P system - Sousa, Pedro (2014)
Nowadays, P2P applications are commonly used in the Internet being an important paradigm for the development of distinct services. However, the dissemination of P2P applications also entails some important challenges that should be carefully addressed. In particular, some of the important coexistence problems existing between P2P applications and Internet Service Providers (ISPs) are mainly motivated by the inherent P2P dynamics which cause traffic to scatter across the network links in an unforeseeable way. In this context, this work proposes a collaborative framework of a Bit- Torrent like system. Using the proposed framework and based on the exchange of valuable information between the application and network levels, some novel techniques are proposed allowing to estimate and control the traffic impact that the P2P system will have on the links of the underlying network infrastructure. Both the framework and the presented techniques were tested resorting to simulation. The results clearly corroborate the viability and effectiveness of the formulated methods.